PENGARUH PEMAHAMAN AKUNTANSI, PENGENDALIAN INTERNAL DAN EFEKTIVITAS PENERAPAN SAP BERBASIS AKRUAL TERHADAP KUALITAS LAPORAN KEUANGAN PADA SKPD KABUPATEN ACEH BARAT DAYA - Intan Rizkia Chudri; Yuslaidar Yusuf; Aldo Gemara (ITB AAS INDONESIA, 2023)
This study aims to examine the effect of accounting understanding, internal control and the effectiveness of accrual-based SAP implementation on the quality of financial reports in SKPD Aceh Barat Daya District. Research data were collected through a list of questions/questionnaires and a study of documentation. Hypothesis testing using multiple linear regression analysis, joint test and partial test is intended to determine jointly and partially the effect of the independent variable on the dependent variable at the 95% confidence level (α = 0.05). This study focuses on understanding accounting, internal control and the effectiveness of accrual-based SAP implementation affects the quality of financial reports at SKPD Aceh Barat Daya Regency. The sample size of this study was 60 employees. The results showed that the simultaneous test of the variables of accounting understanding, internal control and the effectiveness of the accrual-based SAP implementation simultaneously affected the quality of financial reports at the SKPD of Aceh Barat Daya Regency. Then partially, the understanding of accounting has an effect on the quality of financial reports at the SKPD of Southwest Aceh Regency. Internal control affects the quality of financial reports at the SKPD of Southwest Aceh Regency. The effectiveness of the accrual-based SAP application affects the quality of financial reports at the Southwest Aceh District SKPD.